CRISIS MANAGEMENT IN THE DIGITAL AGE - Abduraimov, Muhammadabdullo (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
This study explores the impact of digital technologies on crisis management through a qualitative analysis of secondary data, including literature, reports, and case studies. Findings reveal that social media facilitates rapid information dissemination and real-time engagement, while data analytics enable proactive monitoring and crisis prediction. The study also highlights the role of transparency in fostering public trust and the challenges posed by misinformation. The analysis includes insights from Uzbekistan’s digital transformation, emphasizing the need for continuous adaptation in crisis management practices.